EVALUASI TAHAPAN PUBLIC RELATIONS PROGRAM CORPORATE COMMUNICATION PT. XL AXIATA (STUDI KASUS PELAKSANAAN CSR XL FUTURE LEADERS TAHUN 2012-2016) - Wahyuni, Mentari Tryana; Pascarani, Ni Nyoman Dewi; Alit Suryawati, I Gusti Agung (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
Corporate Social Responsibility Program keep evolving and innovating in various companies in Indonesia, especially since it is defined as an obligation that set forth on Chapter V Article 74 of Law Number 40 Year 2007. XL Axiata is one of the largest telecommunication company in Indonesia that gives a special attention to its CSR program by creating CSR program titled "Persembahan XL untuk Indonesia (XL’s Offering for Indonesia)" and make XL Future Leaders as the flagship program. As a flagship program, XL Future Leaders program has had considerable influence to the company and the environment, but has many obstacles and has been in the final year of implementation. This research was conducted to find out and evaluate the stages of PR that run by department of Corporate Communication as the Public Relations of XL on XL Future Leaders program from 2012 to 2016. This research uses qualitative descriptive method. The result of this research shows that XL's Corporate Communication has done 4 stages of PR in running XL Future Leaders program, which are: first, identifying the problem; second, planning and programming stages; third, taking action and communicating; and fourth, evaluating the program. XL’s Corporate Communication used the same steps and strategies each year as long as the program is implemented, but there are few changes depend on Core business of XL and the conditions of the students' needs at that time. The objectives of this program are well realized although not yet fully achieved   Keywords: Corporate Social Responsibility, PT. XL Axiata, Public Relations stages, XL Future Leaders